(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
This research study focused on the relationship between home background and students’ achievement in mathematics at the senior secondary school level in Rivers State, Nigeria. The ex-post-facto research design was adopted for this study, since already conducted mathematics test scores of the students were retrieved and used for the analysis. Furthermore, data were elicited through the home background and students achievement in mathematics questionnaire (HBSAMQ). A population of 10120 senior secondary II students were involved in the study out of which 4510 were chosen for the sample using the Yarrow Yamen’s formula. The data were analyzed using the Z-test statistic, means and simple percentages. The findings were that there is a significant relationship between home support for mathematics, socio-economic status of parents and students achievement in mathematics.